Pengaruh Layanan Administrasi Kesiswaan Di Sekolah Dan Peran Guru Di Dalamnya Terhadap Kepuasan Perserta Didik - Arif, Muhammad; Hasanah Usnur, Uswatun (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
A school usually has educators or teachers, learners or students, educational staff and facilities that support the educational process. The most important thing in implementing school activities is the students, whose abilities and potential will continue to be developed. The school has a big role in developing the abilities and potential of students, apart from that the school is also responsible for good management so that students get their rights and obligations at school. Therefore, it is necessary to have student administration in every school. Student administration is an important type of administration in an educational institution, especially schools. In general, student administration will relate to all matters relating to students so that student administration must be carried out systematically, regularly, directed and planned in order to support the success of the school in carrying out its roles and responsibilities